Validity of Interactive E-Modules on Plant Growth and Development to Train Students' Science Literacy Skills - Ainun Rohimah; Ulfi Faizah (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2025)
Science literacy is the ability to think scientifically to solve problems and is one of the essential 21st-century skills. However, students’ science literacy in Indonesia remains relatively low and is not yet optimally trained in learning activities. One effort to improve this skill is through the development of interactive e-modules as learning materials. This study aims to develop a valid interactive e-module on plant growth and development to train students' science literacy skills. The research consists of three stages: observation, design, and validity assessment. Validity was reviewed by media and subject matter experts using a validation instrument covering presentation, content, and language aspects, assessed on a 4-point Likert scale (1 = not valid to 4 = very valid). The results were analyzed using Aiken’s V to determine the level of agreement among validators. The developed e-module contains features such as Go Search, Go Wonder, Go Plan, and Go Found, which are integrated with science literacy indicators. The average Aiken index for all aspects was 1.00, indicating a high level of validity. Based on the findings, the interactive e-module is considered valid and feasible to be used as a teaching material to support the development of science literacy skills in high school students.